Skeletal muscle mass index as a predictor of long-term cirrhosis onset in young non-cirrhotic males with acute-on-chronic liver failure - Bai, Jie; Xu, Manman; Peng, Fengling; Gong, Junwei; Zhao, Jinqiu; Song, Xiaodong; Li, Yongguo (Frontiers in Nutrition, 2022)
Background The relationship between skeletal muscle mass index (SMI) and cirrhosis incidence in patients with non-cirrhotic acute-on-chronic (ACLF) has not been clarified. This study aimed to assess the predictive value of SMI on the incidence of long-term cirrhosis in male non-cirrhotic ACLF patients. Materials and methods Male ACLF patients who were free of liver cirrhosis were retrospectively included in this study. Univariate and multivariate logistic analyses were conducted to determine the risk factors for the long-term (1-year) development of cirrhosis. The receiver operating characteristic curves (ROC) were used to assess the ability of SMI levels to predict the incidence of cirrhosis. Restricted triple spline (RCS) described the dose-response relationship between SMI and the risk of cirrhosis. Subgroup analysis was stratified by age (≤ 40 years and > 40 years). Results A total of 230 subjects were included in this study, of whom 45.2% (104/230) were diagnosed with cirrhosis within 360 days. Patients who progressed to cirrhosis had a lower SMI [46.1 ± 6.9 versus 49.2 ± 6.5 cm2/m2, P = 0.001] and a higher proportion of sarcopenia (19.2% versus 6.3%, P = 0.003). In multivariate logistic regression, SMI remained a protective agent against 360-days progression to cirrhosis in males with ACLF after adjustment (OR 0.950, 95% CI: 0.908–0.994, P < 0.05). SMI exerted a non-linear dose-dependent effect on the risk of cirrhosis. The area under the ROC curve (AUC) for the L3-SMI to predict the incidence of cirrhosis in male non-cirrhotic ACLF patients was 0.636 (P < 0.001). We observed significant differences in SMI among male ACLF patients in different age groups. Further subgroup analysis by age revealed that lower SMI was associated with the 1-year incidence of cirrhosis in male ACLF patients aged less than 40 years (OR 0.908, 95% CI: 0.842–0.979, P < 0.05), whereas SMI did not affect the 1-year risk of cirrhosis in older subjects (age > 40 years). Conclusion A higher SMI represents an independent protective factor for developing long-term cirrhosis in male ACLF patients who do not experience cirrhosis, especially in those under 40 years of age.